Intuition Characteristics of Student in Mathematical Problem Solving in Cognitive Style - Megasari Wuryanie; Teguh Wibowo; Nila Kurniasih; Isnaeni Maryam (Department of Mathematics Education, Faculty of Teacher Training and Education, Wisnuwardhana University of Malang, 2020)
This study aims to describe the student's intuition characteristics in solving mathematical problems in the cognitive style Field Dependent (FD) and Field Independent (FI). Source of data comes from students taken with a purposive technique. Data collection techniques using tests, field notes, and interviews. The data validity inspection technique used triangulate technique. Data analysis techniques used data reduction, data display, and conclusion drawing. Based on the results of the study concluded that: students with a Field Dependent (FD) cognitive style used intuition with direct, self-evident, extrampolativeness, intrinsic certainly, coerciveness, and conclusive characteristics. While students with Field Independent (FI) cognitive style use intuition with direct, extrampolativeness, self-evident, intrinsic certainly, coerciveness, and conclusive characteristics. In addition, there are also characteristics that are not found in Field Dependent students, there are globality and one of the anticipatory intuition characteristics (trying hard to solve problems).